The Effect Of Using Profile Picture Of Facebook Strategy In Teaching Writing Descriptive Text Of Eleventh Grade Students At SMA SINGOSARI DELITUA - Laura Thresia Manalu (Jurnal Scientia, 2022)
English is one of the most important international languages ​​for communication. In Indonesia, English is a second language as well as a foreign language. Every school in Indonesia is always given education in a second language, namely English. By learning English, students will be taught four important skills, namely listening, speaking, reading, and writing. Many students in Indonesia have difficulty and feel bored in learning English, especially in learning descriptive text. Therefore, the media used by the teacher must be appropriate and enjoyable for them. Using Facebook profile pictures helps students in learning descriptive text. In addition, students will get new experiences in writing descriptive texts and they will not feel bored. The purpose of this study was to determine whether the Facebook profile picture media was effective or not in learning descriptive texts in class XI SMA Singosari Delitua. In this study, the researchers took 20 students as a sample. As an experimental group, the researcher used class XI IPA which consisted of 10 students, while as a control group, the researcher took 10 students from class XI IPS. Then the researcher gave pre-test and post-test for both assessments. The researcher taught descriptive text using facebook profile picture media to the experimental group and general material from textbooks to the control group. The mean score of the pre-test in the perimental class was 51.7 and the post-test was 84.9. The mean pre-test score in the une control group was 63 and the post-test was 70. This was done so that the average score of the experimental group was higher than the control group. The results of the t-count t-table as a significance level of p-0.05 (9.93 > 1.734). The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So, it can be stated that the hypothesis "the use of Facebook profile pictures for learning to write descriptive texts in class XI students of SMA Singosari Delitua for the academic year 2022/2023 is effective" is accepted. Keywords: Descriptive text, Students, Facebook, Writing